VD_FINDINFO Arrêt / 2025 / 169 vom 21. Februar 2025 - VD Tribunal cantonal (2025)
FORCE PROBANTE, ATTEINTE À LA SANTÉ PHYSIQUE, EXPERTISE | 28 al. 1 LAI, 4 al. 1 LAI, 6 LPGA, 7 al. 1 LPGA, 8 al. 1 LPGA